Workload Comparison of Contemporary Interval Throwing Programs and a Novel Optimized Program for Baseball Pitchers - Brittany Dowling; Christopher M Brusalis; John T Streepy; Alexander Hodakowski; Patrick J Pauley; Dave Heidloff; Grant E Garrigues; Nikhil N Verma; Glenn S Fleisig (International Journal of Sports Physical Therapy)
# Background